Pengaruh Kadar Suspensi Pati Kulit Pisang Kepok pada Kinetika Reaksi Proses Hidrolisis: Kadar Suspensi Pati Kulit Pisang Kepok - Neneng Purnamawati; Arief Yandra (UIR Press, 2021)
Banana peel is one of the wastes that can pollute the environment so it needs to be utilized. One of the ingredients in kepok banana peels is starch (carbohydrates). Banana peel starch can be converted into glucose by hydrolysis method. This study aimed to find out the effect of banana peel starch suspension levels on the reaction kinetics of the hydrolysis process. The hydrolysis process used 2 N oxalic acid with reaction times of 10, 20, 30, 40 and 50 minutes and the levels of suspension of kepok banana peel starch (gr/mlcamp) were 10/250, 20/250 and 30/250. The results showed that the optimum results were obtained at a suspension content of 10/250 gr/ml with a reaction conversion reaching 35% at a time of 50 minutes at a constant temperature of 100°C. Keywords : Hydrolysis, Banana Kepok, Reaction Kinetics